Prevalence of co-occurring conditions among youths receiving treatment with primary anxiety, ADHD, or depressive disorder diagnoses - Ware, Orrin D.; Zerden, Lisa D.; Duron, Jacquelynn F.; Xu, Yanfeng; McCarthy, Lauren P.; Verbiest, Sarah; Afkinich, Jenny; Brown, Qiana; Williams, Denise Yookong; Goings, Trenette (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction: Anxiety disorders, depressive disorders, and attention-deficit/hyperactivity disorder (ADHD) are some of the most common conditions that youths (≤ 18 years old) receive mental health treatment for. These conditions are associated with high-risk substance use or substance use disorders (SUDs). This study sought to identify the proportion of youths (≤ 18 years old) with anxiety disorders, depressive disorders, or ADHD as a primary diagnosis in community mental health centers (CMHCs) having co-occurring high-risk substance use or a SUD. Methods: Analysis included binary logistic regression models using the Mental Health Client-Level Data 2017 to 2019 datasets which contains annual cross-sectional administrative data from mental health treatment facilities. The final sample included n = 458,888 youths with an anxiety disorder as a primary diagnosis, n = 570,388 youths with a depressive disorder as a primary diagnosis, and n = 945,277 youths with ADHD as a primary diagnosis. Results: In the subsample with anxiety as a primary diagnosis, approximately 5% of youth had high-risk substance use or a SUD. Approximately 10% of youth with depression as a primary diagnosis had high-risk substance use or a SUD. Among youth with ADHD as a primary diagnosis, 5% had high-risk substance use or a SUD. Odds of having a co-occurring high-risk substance use or SUD differed based on the youth's age, region, race and ethnicity, gender, and their number ofother mental health diagnoses. Conclusions: Effective care for this high-need youth population at CMHCs will require mental health clinicians to possess knowledge and skills related to substance use treatment.